The traditional ecological knowledge of the local people of Cijambu Village, Sumedang, Indonesia, on the diversity, utilization, management, and conservation of bamboo - MUHAMMAD IHSAN; BUDI IRAWAN; JOHAN ISKANDAR (Society for Indonesian Biodiversity, 2024)
Abstract. Ihsan M, Irawan B, Iskandar J. 2024. The traditional ecological knowledge of the local people of Cijambu Village, Sumedang, Indonesia, on the diversity, utilization, management, and conservation of bamboo. Biodiversitas 25: 1754-1770. Bamboos have been known to play an important role in the socio-economic, cultural, and ecological benefits of rural people in West Java. However, many bamboo gardens have been converted to other land-use types, including commercial vegetable gardens. The study aimed to record local people's Traditional Ecological Knowledge (TEK) in Cijambu, Sumedang, West Java, Indonesia, regarding the diversity, utilization, management, and conservation of ethnobotany and bamboo. The mixed method, combining approaches with an ethnobotanical perspective, was employed in this study through semi-structured and structured interviews with informants. The study results showed a diversity of bamboo landraces with six types of bamboo identified by the community: Awi Tali (Gigantochloa apus), Awi Gombong/Awi Surat (Gigantochloa verticillata), Awi Temen (Gigantochloa atter), Awi Bitung (Dendrocalamus asper), Haur Héjo (Bambusa vulgaris var. vulgaris), and Haur Konéng (Bambusa vulgaris var. striata). Bamboo has 41 uses: 3 ecological uses, 32 economic uses, and 6 socio-cultural uses. Bamboo management involves maintaining and transforming bamboo gardens into mixed gardens, combining vegetables and coffee plants to increase income. Community conservation efforts involve selective logging to ensure the sustainability and regeneration of bamboo. The conservation process is influenced by cultural beliefs and myths, such as refraining from cutting or taking bamboo on Fridays. Bamboo people believe in Tolak Bala, which uses Haur Konéng bamboo.